Diplomatic strategies of the Patani kingdom in Hikayat Patani: a sociology of literature study - Islahuddin Islahuddin; Ku-Ares Tawandorloh; Sumaiyah Menjamin (BAHASTRA, 2021)
Hikayat Patani is a saga that tells of the Patani kingdom and various diplomatic strategies contained in the Patani kingdom. The aim of this research is to describe various texts that discuss the diplomatic strategy of the Patani kingdom in Hikayat Patani by using a literary of sociology approach. This research is sourced from the data of Hikayat Patani. The data collection techniques using reading and noting techniques. The data analysis technique uses a qualitative descriptive technique accompanied by a theory of literary of sociology. The results of the study show that diplomatic strategies of Patani kingdom in Hikayat Patani namely: 1) political diplomacy with Siam; 2) war diplomacy with Siam and Palembang; 3) marital diplomacy with Pahang and Johor; 4) trade diplomacy with Cina and Melaka; 5) power diplomacy with Kelantan; and 6) religious diplomacy with Pasai. Moreover, the results of the research show that the diplomatic strategies of Patani kingdom contained in Hikayat Patani are aims to maintain and maintain the honor of the kingdom as a sovereign kingdom and a mirror of Patani society at the time the text was created.